Strengthening Zakat Rules in Indonesia: A Legal Study of the Law on the Government of Aceh - Faisal, Faisal; Mukhlis, Mukhlis; Jamaluddin, Jamaluddin; Manfarisyah, Manfarisyah; Maghfirah, Fitri (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Aceh is a province with special authority under the Law Number 11 of 2006 on the Government of Aceh (Undang-Undang Pemerintahan Aceh/UUPA). The special authority is mentioned, among other regulations, in Article 180, which makes zakat the source of original income of the Aceh Region and the district or city. This study is a normative juridical research, that is, a study that analyses the regulations of laws that set law as a system of norms.The data collection technique used in this research is a literature studies of laws and regulations. This study concludes that zakat management in Aceh is regulated based on the UUPA of 2006. Baitul Mal Aceh and Baitul Mal districts or cities manage the institutions that regulate it. In addition, this legal regulation also explains that the amount of zakat paid is a deductible expense from the taxpayer's income tax liability. However, the existence of zakat, as stipulated in a number of UUPA articles, has not been implemented as expected. The absence of government regulations governing the implementation of taxes as a deductible factor for the amount of income tax payable is one of the reasons for not implementing Article 192. This government regulation is an essential factor towards strengthening the law on the Government of Aceh as part of the Helsinki Memorandum of Understanding mandate. The principle of lex specialis derogate lex generalis must be used as a legal argument in order to encourage the implementation of these regulations. Since Aceh is a region with special autonomy, the application of its law must also be handled specifically.